Pengaruh Periode Penyemprotan dan Waktu Germinasi terhadap Karakteristik Tepung Beras Cokelat Germinasi - Prasongko, Prasongko; Budi, Faleh Setia; Faridah, Didah Nur (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Substituting wheat flour with rice flour in brownies premix formulations presents has remained a great task as the flour has a higher setback viscosity (SV) which accelerates staling. To resolve this problem, germination process was needed to modify brown rice. This research aimed to investigate the effect of spraying period and germination time on the characteristics of germinated brown rice (GBR) flour, to determine the optimal germination conditions that yield SV values closest to those of wheat flour. Besides, correlation between SV of GBR flour and others was observed. In germination process, brown rice was subjected to spraying intervals of 15 and 20 min and germination times of 18, 24, and 30 h. Furthermore, the germinated brown rice was drained, dried, and milled into flour. While low protein wheat flour was used as control, ungerminated brown rice flour was also included for comparison. As a result, the treatment of spraying period of 20 min and germination for 24 h produced GBR flour with SV (1024 cP), closely resembling the control (972 cP). In addition, the GBR flour had peak viscosity (PV) 1520 cP, trough viscosity (TV) 375 cP, breakdown viscosity (BV) 1144 cP, final viscosity (FV) 1400 cP, peak time 8.8 min, pasting temperature 84.3 °C, germination percentage 93.2%, dextrose equivalent (DE) 2.627%, water adsorption index (WAI) 7.609, water solubility index (WSI) 14.237%, and swelling power (SP) 8.872. Moreover, SV was positively correlated with WAI and SP, but negatively correlated with germination percentage, DE, and WSI. The strongest correlation was observed between SV and WSI (r= -0.906).